Kompetensi Anggota DPRD Dalam Mendukung Fungsi Pengawasan Terhadap Pemerintah Daerah - Ma'ruf, Muhammad Farid (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2019)
Political decentralization has the consequence of placing the Regional Representative Council (DPRD) in an equal position with the regional head in the administration of regional government. Strengthening the DPRD's institutional function is realized in the Legislation, Budgeting and Controling as the functions of repsentative institusion in the central level. However, The council is considered unable to carry out its functions properly including carrying out the oversight function of planning, implementing activities and local government programs. Based on these conditions, the researchers conducted a competency study of DPRD members in tracking the supervisory function in Gresik Regency. The results, showed that the supervisory process and mechanism carried out by the DPRD had not led to 4 basic stages of supervision; a) Establish standards, b). Measurement performance, c). Comparable performance agains standars and d) Consider correction action. It’s still not done systematically, so the implementation of supervision of the council in Gresik which is translated into commission board still considered sporadic and partial activities. The commission oversight agenda summarized in the work meeting activities, public hearings and work visits of each commission has not yet become an integral activity of a monitoring process. The conclusion, there are gaps between the critical competencies of councill’s members about functions as members of representative institutions. The gap is related to the vision, mission, insights and technical conceptions of each member's task in the field. Supervision task carried out by the Gresik’s council is not systematic and seems sporadic.